The Cognitive Mechanism of the Practice Effect of Time-Based Prospective Memory: The Role of Time Estimation - Gan, Jiaqun; Guo, Yunfei (Frontiers in Psychology, 2019)
Remembering to perform delayed intentions at a specific time point or period is referred to as time-based prospective memory (TBPM). The practice effect of TBPM is the phenomenon that TBPM performance improves via repeated PM training. In the present study, our main purpose was to explore the cognitive mechanism of the practice effect of TBPM, specifically the role of time estimation in the practice effect. We adopted a simple retrospective component of TBPM (pressing 1 key) in the present study, facilitating a closer look at the role of time estimation. In Experiment 1, the experimental group received 20 TBPM tasks training and some ongoing tasks training, while the control group only received some ongoing tasks training. We found that TBPM and time estimation abilities of experimental group were all better than those of control group. It proved that the practice effect of TBPM was closely related to the improvement of time estimation ability. In Experiment 2, we used time estimation training instead of TBPM training used in Experiment 1. The results of Experiment 2 were basically the same as those of Experiment 1. It further confirmed that time estimation played a key role in the practice effect of TBPM.